Impact of transportation duration on stress responses in day-old chicks from young and old breeders. (June 2017) - Jacobs, Leonie; Delezie, Evelyne; Duchateau, Luc; Goethals, Klara; Ampe, Bart; Buyse, Johan; Tuyttens, Frank Andre Maurice
Abstract: The aim of this study was to assess the interaction effect of transportation duration and parental age on physiological stress responses and quality in day-old chicks. After hatch, 3240 chicks from either 29-week old (young) or 60-week old (old) broiler breeders were transported for 1.5 h (short) or 11 h (long). Thereafter, 228 chicks were assessed for quality and blood plasma was assayed for corticosterone (CORT), lactate, glucose, and thiobarbituric acid-reactive substances (TBARS, increased concentrations can indicate oxidative stress). No interaction effects of parental age and transportation duration were found (all P  > 0.10). Chicks from young breeders showed higher CORT levels ( P  = 0.007) and were of higher quality (Tona method, P  < 0.001) than those from old breeders. After long transportation, chicks showed increased CORT ( P  < 0.001) and lower TBARS levels ( P  < 0.001) compared to after short transportation. No evidence was provided that long transportation differently affected the quality or stress responses of chicks from breeder flocks of two ages. Highlights: Chicks from young or old breeder flocks did not respond differently to short or long transportation. Corticosterone levels and chick quality scores (Tona method) were higher in chicks from young breeders. Corticosterone levels were increased after long transportation. Thiobarbituric acid-reactive substances were lower after long transportation.